PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK) PERIODE 2019-2021 - Mulyani, Any Fitriya; Manunggal, Syafrudin Arif Marah (Politeknik Negeri Ambon, 2023)
The purpose of this study was to test and analyze the effect of the Capital Adequency Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Assets (ROA) and Debt to Equity Ratio (DER) on stock prices. The objects of this research are banking companies listed on the Indonesia Stock Exchange in 2019-2021. The population in this study were all banking companies listed on the Indonesia Stock Exchange, namely 106 banks. Determination of the sample using purposive sampling method, with a total sample of 25 banking companies that have certain criteria. The method used is panel data regression analysis with the help of the E-Views 12 application. The results of this study partially indicate that Return on Assets (ROA) loan to Deposit ratio (LDR) and Capital adequacy ratio (CAR) has a significant positive effect on stock prices. Meanwhile, Debt to Equity Ratio (DER) have no significant effect on stock prices on the Indonesia Stock Exchange (IDX) for the 2019-2021 period